(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Substance classified as retro-reflective is used to make the cloak, which is used for visual conceal ment purposes. Particles of retro-reflective substance occupy a broad surface area. It’s impossible to tell where the flashes of illumination come from as they hit these beads. Utilizing the color information of a certain colour, we must obscure the picture’s backdrop in this applica tion. I’m utilizing red, black, blue, and white to create the above notion. The programme will translate the shade to HSV style and pick the correct top and bottom limit val ues to identify the hue variations and then conceal it if the colour is present in the picture.